It’s time for psychoneuroimmunology to focus on Asian health practices and medicine:Introducing Brain, Behavior, and Immunity-Integrative - Zou, Liye (The Journal of the International Society of Chinese Health Practices, 2024)
As the founding Co-Associate Editors,the Editor-in- Chief and Elsevier, we are excited to pen this article that launches a new bio-medical research journal, Brain, Behavior, and Immunity–Integrative(BBI-Integrative). In 1987,the first Editor-in-Chief of another new journal, Robert Ader and colleagues wrote the first paper published inBrain, Behavior, and Immunity(BBI, Ader et al.,1987). In 1998, the Psychoneuroimmunology Research Society(PNIRS) membership approved a resolution for BBI to become its official journal. After negotiations with leading publishing houses, on January 1,2000, BBI be-came the official journal of PNIRS (Kelley,2001). At that time, BBI wasowned by Academic Press. Within three short years, Elsevier acquire downership of BBI and appointed Keith W.Kelley as the new Editor-in-Chief. He wrote a lead editorial following his appointment(Kelley,2003). Carmine Pariante was subsequently appointed to this position in2018, at which time he laid out his goals for BBI (Pariante,2018). Two years later,the Board of Directors of PNIRS and Elsevier approved publication of the first sister journal of BBI, Brain, Behavior, and Immunity–Health (BBI-Health). Carmine Pariante and colleagues described why this sister journal of BBI was needed(Cattaneo et al,2020). Now, both PNIRS and Elsevier are expanding the scope of psychoneuroimmunology(PNI) research by launching a second official companion journal of PNIRS, BBI-Integrative. This new journal is needed because it focuses on Asian health practices and medicine.